The Feasibility of Implementing Targeted SEDation in Mechanically Ventilated Emergency Department Patients: The ED-SED Pilot Trial*. Issue 8 (11th April 2022) - Fuller, Brian M.; Roberts, Brian W.; Mohr, Nicholas M.; Faine, Brett; Drewry, Anne M.; Wessman, Brian T.; Ablordeppey, Enyo; Pappal, Ryan D.; Stephens, Robert J.; Sewatsky, Thomas; Cho, Nicholas S.; Yan, Yan; et al.
Abstract : OBJECTIVES: Deep sedation in the emergency department (ED) is common, increases deep sedation in the ICU, and is negatively associated with outcome. Limiting ED deep sedation may, therefore, be a high-yield intervention to improve outcome. However, the feasibility of conducting an adequately powered ED-based clinical sedation trial is unknown. Our objectives were to assess trial feasibility in terms of: 1) recruitment, 2) protocol implementation and practice change, and 3) safety. Patient-centered clinical outcomes were assessed to better plan for a future large-scale clinical trial. DESIGN: Pragmatic, multicenter ( n = 3), prospective before-after pilot and feasibility trial. SETTING: The ED and ICUs at three medical centers. PATIENTS: Consecutive, adult mechanically ventilation ED patients. INTERVENTIONS: An educational initiative aimed at reliable ED sedation depth documentation and reducing the proportion of deeply sedated patients (primary outcome). MEASUREMENTS AND MAIN RESULTS: Sedation-related data in the ED and the first 48 ICU hours were recorded. Deep sedation was defined as a Richmond Agitation-Sedation Scale of –3 to –5 or a Sedation-Agitation Scale of 1–3. One thousand three hundred fifty-six patients were screened; 415 comprised the final population. Lighter ED sedation was achieved in the intervention group, and the proportion of deeply sedated patients was reduced from 60.2% to 38.8% ( p < 0.01). There were no concerning trends in adverse events (i.e., inadvertent extubation, device removal, and awareness with paralysis). Mortality was 10.0% in the intervention group and 20.4% in the preintervention group ( p < 0.01). Compared with preintervention, the intervention group experienced more ventilator-free days [22.0 (9.0) vs 19.9 (10.6)] and ICU-free days [20.8 (8.7) vs 18.1 (10.4)], p < 0.05 for both. CONCLUSIONS: This pilot trial confirmed the feasibility of targeting the ED in order to improve sedation practices and reduce deep sedation. These findings justify an appropriately powered clinical trial regarding ED-based sedation to improve clinical outcomes.